Effect of gingival fibroblasts and ultrasound on dogs' root resorption during orthodontic treatment - Jacqueline Crossman; Ali H Hassan; Ali Saleem; Nayef Felemban; Saleh Aldaghreer; Elham Fawzi; Mamdouh Farid; Khaled Abdel-Ghaffar; Ausama Gargoum; Tarek El-Bialy (Wolters Kluwer Medknow Publications, 2017)
Objectives: To investigate the effect of using osteogenic induced gingival fibroblasts (OIGFs) and low intensity pulsed ultrasound (LIPUS) on root resorption lacunae volume and cementum thickness in beagle dogs that received orthodontic tooth movement. Materials and Methods: Seven beagle dogs were used, from which gingival cells (GCs) were obtained and were induced osteogenically to produce OIGFs. Each third and fourth premolar was randomly assigned to one of the five groups, namely, LIPUS, OIGFs, bone morphogenetic protein-2 (BMP-2), OIGFs + LIPUS, and control. All groups received 4 weeks of bodily tooth movement, then LIPUS-treated groups received LIPUS for 20 min/day for 4 weeks, and OIGFs groups received an injection of OIGFs near the root apex. Microcomputed tomography analysis was used to calculate root resorption lacunae volume and histomorphometric analysis was performed to measure the cementum thickness of each root at 3 root levels on compression and tension sides. Results: There was no significant difference in resorption volume between the treatment groups. OIGFs + LIPUS increased cementum thickness (P > 0.05) in third premolars near the apex, and LIPUS increased cementum thickness (P > 0.05) in fourth premolars near the apex. Furthermore, BMP2 increased cementum thickness at the coronal third at the compression side. Conclusion: OIGFs, LIPUS, and BMP-2 can be potential treatments for orthodontically induced root resorption, however, improvements in experimental design and treatment parameters are required to further investigate these repair modalities.